Cyclic deformation response of ultra-fine grained titanium at elevated temperatures. (May 2019) - Sajadifar, S.V.; Yapici, G.G.; Demler, E.; Krooß, P.; Wegener, T.; Maier, H.J.; Niendorf, T.
Highlights: Fatigue of UFG Ti at temperatures up to 600 °C is investigated. Effect of processing route is investigated. Improved fatigue performance up to 400 °C is demonstrated. Strain path does not have strong affect on the fatigue behavior when comparing routes Bc and E. Abstract: This study focuses on the high-temperature cyclic deformation response (CDR) of ultra-fine grained (UFG) titanium of commercial purity (grade 4) processed via equal channel angular extrusion as a severe plastic deformation method. Low-cycle fatigue experiments were conducted at elevated temperatures up to 600 °C and at strain amplitudes ranging from 0.2% to 0.6%. Besides temperature and strain amplitude, the influence of two processing routes (8BC and 8E) on the fatigue characteristics of UFG Ti was examined. It is clearly revealed that the CDR of UFG Ti is not strongly affected by the alteration of strain path during ECAE processing, as long as highly efficient routes are employed. Both routes lead to high volume fraction of high angle grain boundaries and improved fatigue performance up to 400 °C is demonstrated. Electron backscatter diffraction assisted microstructural characterization was used to analyze elementary degradation mechanisms affecting cyclic mechanical behavior. Micrographs reveal the occurrence of severe recrystallization and grain growth only at temperatures above 400 °C and, thus, grade 4 UFG Ti is characterized by unprecedented cyclic stability in comparison to other UFG alloys.